Local Events, Global Effects: Transcendent Emotions and Identification with All Humanity - Pizarro, José J. (2021)
Confronted with the challenges of the globalized world, recent research suggests that identification with humanity has socio-affective roots and is driven by the celebration of collective rituals that promote benevolence and universalism. This paper analyzes the relation of a self-transcendent emotion (i.e., Awe) lived in local collective meetings with human identity. We conducted a across-sectional study in Mexico and the Basque Country (N = 656), and the results of structural equation modelling shows that this emotion increases the identification with humanity, well-being (directly) and prosocial behavior (indirectly). Further, the intensity of this emotion also predicted the perception of emotional synchrony while controlling for more stable and trait-alike variables. Following Durkheim, the emotional processes experienced in collective events encourage the development of shared identities and the promotion of the common welfare through experiences of self-transcendence, which can result of great importance in the common efforts to deal with current large-scale social issues.